2017
DOI: 10.25226/bboc.v137i1.2017.a8
|View full text |Cite
|
Sign up to set email alerts
|

Range extension for Buff-fronted OwlAegolius harrisiiin north-east Brazil and a case ofHeterochromia iridisin Strigidae

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…3). It has only been in the past five years, however, that the first records have been obtained from the state of Alagoas (Rodrigues 2013) and the Atlantic Forest of Sergipe (Ruiz-Esparza et al 2017). In Pernambuco (Oliveira 2018) and Alagoas (Rodrigues 2013), A. harrisii has been documented by photographs but without additional information provided on the habitat.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3). It has only been in the past five years, however, that the first records have been obtained from the state of Alagoas (Rodrigues 2013) and the Atlantic Forest of Sergipe (Ruiz-Esparza et al 2017). In Pernambuco (Oliveira 2018) and Alagoas (Rodrigues 2013), A. harrisii has been documented by photographs but without additional information provided on the habitat.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, additional data have been gathered and new aspects of the natural history of this species, including its vocalizations and habitat preferences, have been described (e.g. Braun et al 2003;Córdoba and Ahumada 2005;Bodrati and Cockle 2006;Ubaid et al 2012;Bravo and Barrio 2014;Ramoni-Perazzi et al 2014;Ruiz-Esparza et al 2017;Penagos et al 2018). Although these studies have provided important insights into the ecological preferences of the species, most of its life history traits remain poorly understood, and the number and size of its populations are probably underestimated (Enríquez 2015;Girão and Albano 2010;Rosa et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterochromia iridis, in which the two irises of a single individual are different colors, has also been reported in several species of birds but seems to be uncommon (Poor 1946, Ryan 2013, David et al 2013, Ruiz-Esparza et al 2017, Kinney et al 2017). However, a study of Common Cuckoos (Cuculus canorus) found a consistent tendency for the left eye to have more extensive dark flecking than the right eye (Yoo et al 2017) -although the mechanism and significance of this tendency is unknown -and few studies have sought to quantify these types of differences.…”
Section: Variation In Eye Color Within Speciesmentioning
confidence: 98%
“…lidad: vocaliza en cortos períodos del año y en épocas distintas, responde a la reproducción de sus voces (playback) solo en ciertas circunstancias, y sus vocalizaciones pueden ser confundidas con ranas, insectos y otras lechuzas (Olrog 1985, König 1999, Bodrati & Cockle 2006, Girão & Albano 2010, Bodrati et al 2016. En los últimos 15 años, nuevos registros ampliaron el conocimiento de su distribución y actualizaron su presencia en distintas regiones de Sudamérica (Bodrati & Cockle 2006, Ribas & Santos 2007, Barrionuevo et al 2008, Kaminski 2009, Santos 2009, Girão & Albano 2010, Rebelato et al 2011, Azpiroz et al 2012b, Pereira et al 2012, Ubaid et al 2012, Bravo & Barrio 2014, Santos et al 2014, Cadena-Ortiz et al 2015, Bodrati et al 2016, Dornas et al 2017, Ruiz-Esparza et al 2017, Penagos et al 2018. Sin embargo, el conocimiento de su biología sigue siendo muy limitado.…”
unclassified